Not quite ripe : a memoir - Byrne, Debra (Pac Macmillan Australia, 2006)
Her life has been roller-coaster ride of successes and adulation alongside scandal, drugs and depression. From her first showbiz triumphs on 'Young Talent Time', Debra's existence had a darker side. From childhood abuse to underage sex, from the destructive evil of drug addiction and depression, Debra still managed her performances.